Effects of transcutaneous electrical nerve stimulation (TENS) and interferential currents (IFC) in patients with nonspecific chronic low back pain: randomized clinical trial - Facci, Ligia Maria (2011)
CONTEXT AND OBJECTIVE: Transcutaneous electrical nerve stimulation (TENS) and interferential current are the most used electrotherapy methods, although there is little scientific evidence to support their use. The aim of this study was to compare the effects of TENS and interferential current among patients with nonspecific chronic low back pain. DESIGN AND SETTING: Single-blind randomized controlled trial in the Department of Physiotherapy, Centro Universitário de Maringá. METHODS: One hundred and fifty patients were randomly divided into three groups: TENS (group 1), interferential current (group 2) and controls (group 3). The patients designated for electrotherapy received ten 30-minute sessions, while the control group remained untreated. All patients and controls were evaluated before and after treatment using a visual analog scale and the McGill Pain and Roland Morris questionnaires, and regarding their use of additional medications. RESULTS: There was a mean reduction on the visual analog scale of 39.18 mm with TENS, 44.86 mm with interferential current and 8.53 mm among the controls. In the Roland Morris questionnaire, group 1 had a mean reduction of 6.59; group 2, 7.20; and group 3, 0.70 points. In group 1, 84% of the patients stopped using medications after the treatment; in group 2, 75%; and in group 3, 34%. There was no statistically significant difference between the TENS and interferential current groups (P > 0.05); a difference was only found between these groups and the controls (P < 0.0001). CONCLUSION: There was no difference between TENS and interferential current for chronic low back pain treatment. CLINICAL TRIAL REGISTRATION: NCT01017913.